Multiphysics methodology for thermal modelling and quantitative analysis of electromagnetic linear actuator. (19th July 2019) - Tan, Cao; Li, Bo; Liu, Yongteng; Ge, Wenqing; Sun, Binbin
Abstract: Multiphysics methodology is a preferred tool for the design and optimization of electromagnetic linear actuators (EMLA). In this paper, a multiphysics method was proposed, which uses the non-simplified energy consumption distribution as the heat source for temperature field calculation, adjusts the material properties by temperature, and considers the interaction between motion (including impact) and loss. Then comprehensive experiments and quantitative analysis were carried out. The results show that the errors between simulated and experimental results of indices such as landing velocity, input circulating energy, iron loss and temperature rise of prototype were less than 5%. The prototype's total iron loss was decreased by 57.6% with fixed armature and dynamic response time was decreased by 10.4% without eddy current compared with the normal condition. This result validated the precision and necessity of the coupling model. In addition to being applied to EMLA, the proposed methodology can be used for analysis and design of a wide range of electromagnetic actuators.